A method for preparing a two-dimensional molybdenum disulfide-based light-responsive antibacterial composite film
Patent Information
- Application Number
- CN202310724294.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-06-19
AI Technical Summary
但是通过液相剥离制备二维二硫化钼的制备过程使用有毒试剂造成二维二硫化钼不适宜用于食品等领域且容易对环境产生不利影响,由于光热抗菌以及活性氧抗菌仅对与二维二硫化钼紧密接触的细菌具有良好的抗菌能力
[0016] (1) The lignin-assisted three-frequency ultrasonic liquid phase exfoliation of molybdenum disulfide used in this invention has a high yield of two-dimensional molybdenum disulfide nanosheets. No toxic reagents are used in the whole process, which is green and environmentally friendly. The operation is simple and suitable for industrial production. The concentration of two-dimensional molybdenum disulfide in water is 1.713 mg/mL, the size is 100~200 nm, and the number of nanosheet layers is less than 5.
Smart Images

Figure CN116535711B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of antibacterial materials technology, specifically relating to a method for preparing a two-dimensional molybdenum disulfide-based photoresponsive antibacterial composite film. Background Technology
[0002] In recent years, the problem of bacterial infections and antibiotic overuse leading to increasingly serious bacterial resistance has become increasingly serious, thus the development of novel antibacterial materials has attracted widespread attention. Two-dimensional molybdenum disulfide (MoD2) possesses a unique layered structure. When excited by infrared light, it converts energy into heat through lattice vibration and electron oscillation. Simultaneously, due to the generation of photogenerated electrons and holes, reactive oxygen species are produced during photoexcitation, giving MoD2 materials excellent antibacterial capabilities. However, the preparation process of MoD2 via liquid-phase exfoliation uses toxic reagents, making it unsuitable for use in food and other fields and potentially causing adverse environmental impacts. Furthermore, photothermal and reactive oxygen species-based antibacterial agents only have good antibacterial activity against bacteria in close contact with MoD2. Additionally, the high rigidity of the MoD2 and polyvinyl alcohol film limits the application range of the composite film. Therefore, developing industrially suitable and environmentally friendly liquid-phase exfoliation technology, increasing the accessibility of MoD2's antibacterial properties, and improving the toughness of composite films to expand their applicability are crucial.
[0003] Lignin is a natural antibacterial component found in plants, the second largest biomass raw material in nature, and a surface-active material with multiple hydroxyl groups. The use of surfactants in liquid-phase exfoliation processes aids in the exfoliation of molybdenum disulfide. Hexagonal tri-frequency ultrasound, through the combination of three different ultrasonic frequencies, possesses a strong ultrasonic cavitation effect and a large sample throughput, making it more suitable for large-scale industrial production. Modified lignin can expose more phenolic hydroxyl structures, thus exhibiting stronger antibacterial capabilities. Reactive oxygen free radicals generated by infrared light excitation can attack lignin molecules, causing the cleavage of chemical bonds within the lignin. Eutectic solvents are eutectic mixtures composed of quaternary ammonium salts or metal salts and hydrogen bond donors. Eutectic solvents have advantages such as low vapor pressure, good solubility, low cost, ease of preparation, non-toxicity, and biocompatibility. Existing research has shown that the addition of small amounts of eutectic solvents can improve the mechanical properties of composite films due to the formation of multiple hydrogen bonds.
[0004] Therefore, the preparation of two-dimensional molybdenum disulfide nanosheets using lignin-based three-frequency ultrasonic liquid-phase exfoliation, while simultaneously introducing lignin, is expected to significantly improve the liquid-phase exfoliation effect and enhance antibacterial properties. Using a eutectic solvent can improve the toughness of the composite film and expand its application range. Summary of the Invention
[0005] To address the above problems, this invention provides a method for preparing a two-dimensional molybdenum disulfide-based photoresponsive antibacterial composite film.
[0006] To achieve the above objectives, the present invention employs the following technical solution: A method for preparing a two-dimensional molybdenum disulfide-based photoresponsive antibacterial composite film, comprising the following steps:
[0007] (1) Synthesis of eutectic solvent: The eutectic solvent is ethylene glycol: choline chloride is stirred at 70°C for several hours in a certain molar ratio until a uniform and transparent liquid is formed;
[0008] (2) Annealing treatment of molybdenum disulfide: under nitrogen protection, molybdenum disulfide is annealed at a certain temperature for several hours to obtain molybdenum disulfide powder with S vacancies;
[0009] (3) Liquid phase stripping of molybdenum disulfide: Molybdenum disulfide powder with S vacancies in step (2), alkali lignin (Sigma), and Milli-Q ultrapure water are mixed in a certain mass ratio, treated with tri-frequency ultrasonication at 30°C for 3 hours, and the unstripped molybdenum disulfide is removed by centrifugation at 10000rpm to obtain a two-dimensional molybdenum disulfide and lignin suspension.
[0010] (4) Preparation of photoresponsive antibacterial composite film: In step (3), two-dimensional molybdenum disulfide and lignin suspension, a certain concentration of polyvinyl alcohol solution and eutectic solvent are mixed in a certain volume ratio, and after being bathed in a water bath at 90°C for 30 minutes, the film is dried at 37°C for 24 hours to obtain photoresponsive antibacterial composite film.
[0011] Preferably, the molar ratio of ethylene glycol and choline chloride in step (1) is 2:1.
[0012] Preferably, the annealing temperature in step (2) is 300°C and the annealing time is 2 hours.
[0013] Preferably, in step (3), the mass ratio of molybdenum disulfide powder, alkali lignin, and Milli-Q ultrapure water is 1:0.05~0.15:100. The ultrasonic frequencies are 20kHz, 40kHz, and 60kHz, the output power is 600W, and the switching pulse is 4 / 1s.
[0014] Preferably, the polyvinyl alcohol concentration in step (4) is 5%, and the solvent is Milli-Q ultrapure water, a two-dimensional molybdenum disulfide and lignin suspension, polyvinyl alcohol, and a low eutectic solvent with a volume ratio of 2:10:0.2.
[0015] The beneficial effects of this invention are:
[0016] (1) The lignin-assisted three-frequency ultrasonic liquid phase exfoliation of molybdenum disulfide used in this invention has a high yield of two-dimensional molybdenum disulfide nanosheets. No toxic reagents are used in the whole process, which is green and environmentally friendly. The operation is simple and suitable for industrial production. The concentration of two-dimensional molybdenum disulfide in water is 1.713 mg / mL, the size is 100~200 nm, and the number of nanosheet layers is less than 5.
[0017] (2) The photoresponsive antibacterial composite film provided by the present invention has excellent mechanical properties, with an elongation at break of 497% and a toughness of 189.9 Mj / m. 3 It has wide application value in the fields of food packaging materials and medical antibacterial materials.
[0018] (3) The photoresponsive antibacterial composite film provided by this invention has strong antibacterial ability. Experiments have shown that after being excited by infrared light at a wavelength of 808 nm for 20 minutes, it can reduce the number of viable Escherichia coli and Staphylococcus aureus in the environment from 7 × 10⁻⁶ to 10⁻⁶. 7 CFU / mL decreased to 1×10 7 The composite film, with a concentration of CFU / mL, still exhibits excellent antibacterial properties even after light exposure has ceased. Attached Figure Description
[0019] Figure 1 These are concentration diagrams of two-dimensional molybdenum disulfide suspensions in Examples 1, 2, 3, and Comparative Example 1.
[0020] Figure 2 These are scanning electron microscope (SEM) images of two-dimensional molybdenum disulfide in Examples 1, 2, and 3, and Comparative Example 1.
[0021] Figure 3 These are images showing the mechanical property test results of the photoresponsive antibacterial composite films prepared in Example 2 and Comparative Example 2.
[0022] Figure 4 These are images showing the antibacterial test results of the photoresponsive antibacterial composite films prepared in Examples 1, 2, 3, and Comparative Example 1. Detailed Implementation
[0023] The present invention will be further described in detail below with reference to specific embodiments. These descriptions are for explanation purposes only and are not intended to limit the scope of the invention.
[0024] The preparation method of a two-dimensional molybdenum disulfide-based photoresponsive antibacterial composite film according to the present invention includes the following steps:
[0025] (1) Concentration test of two-dimensional molybdenum disulfide suspension: The absorbance value at 669 nm was determined by scanning the UV-Vis absorption spectrum of the two-dimensional molybdenum disulfide suspension after three-frequency ultrasonic treatment (Beijing Purkinje, TU-1080). The concentration of the two-dimensional molybdenum disulfide suspension was calculated according to the following formula:
[0026] (1)
[0027] Where A is the absorbance at an absorption wavelength of 669 nm, I is the optical path length of the cuvette, and α is the absorptivity of 2177.09 mL / mg·m.
[0028] Depend on Figure 1 The concentrations of the two-dimensional molybdenum disulfide suspensions in Examples 1, 2, and 3 are higher than those in Comparative Example 1 without lignin. Higher concentrations of two-dimensional molybdenum disulfide suspensions can be obtained under three-frequency ultrasound at 20 kHz, 40 kHz, and 60 kHz and liquid-phase exfoliation with 50-150 mg of lignin.
[0029] (2) The microstructure of the stripped molybdenum disulfide was observed using a scanning electron microscope.
[0030] Depend on Figure 2 The two-dimensional molybdenum disulfide nanosheets of Examples 1, 2, and 3 are significantly smaller than those of Comparative Example 1. Two-dimensional molybdenum disulfide nanosheets with sizes between 100 and 200 nm can be obtained by three-frequency ultrasound at 20 kHz, 40 kHz, and 60 kHz and liquid phase exfoliation with 50-100 mg of lignin.
[0031] (3) Tensile properties of the photoresponsive antibacterial composite film were tested using a stable micro system (TA-XT2i). A rectangular specimen with dimensions of 1 × 6 cm was prepared, and a tensile test was performed according to ASTM D882 standard. The tensile speed was 50 mm / min, and the distance between the two sides was 2 cm.
[0032] Depend on Figure 3 The photoresponsive antibacterial composite film in Example 2 showed significantly higher elongation at break and toughness than that in Comparative Example 2. The addition of 200 μL of a eutectic solvent imparted even better mechanical properties to the photoresponsive antibacterial composite film.
[0033] (4) Antibacterial ability test of photoresponsive antibacterial composite film: Escherichia coli and Staphylococcus epidermidis were cultured to the logarithmic phase, and the bacteria were washed with sterile physiological saline solution (0.9% NaCl). Then the bacterial density was adjusted to about 10. 7 CFU / mL. Then, 200 μL of the bacterial suspension was added to a 48-well plate, along with a 1 cm diameter light-responsive antibacterial composite film disc. The plate was placed in the dark for 60 min, followed by light-responsive antibacterial treatment using a 1.5W 808nm infrared lamp for 20 min. After the light exposure, a certain amount of the bacterial suspension was diluted and spread onto LB agar, then incubated at 37℃ for 24 h. The colony count was then determined for each sample, with untreated bacteria serving as a blank control.
[0034] Depend on Figure 4 The results show that the photoresponsive antibacterial composite films in Examples 1, 2, and 3 have excellent photoresponsive antibacterial capabilities, while Comparative Example 1 has weak antibacterial capabilities due to the absence of lignin.
[0035] (5) Test of antibacterial ability of photoresponsive antibacterial composite film under no light after photoexcitation: Escherichia coli and Staphylococcus epidermidis were cultured to the logarithmic phase, and the bacteria were washed with sterile physiological saline solution (0.9% NaCl). Then the bacterial density was adjusted to about 10. 7 CFU / mL was spread onto LB solid medium. After irradiation with infrared light for 20 minutes, a 1 cm diameter photoresponsive antibacterial composite film disc was placed on the LB medium coated with bacteria. The medium was then incubated in a 37°C biochemical incubator for 24 hours, and the size of the inhibition zone was counted.
[0036] Table 1. Test results of the antibacterial ability of the photoresponsive antibacterial composite film in the absence of light.
[0037] Example 1 1.51 Example 2 1.34 Example 3 1.24 Comparative Example 1 0.00
[0038] Table 1 shows that Examples 1, 2, and 3 still have high antibacterial ability after being excited by infrared light in the absence of light, while Comparative Example 1 has weak antibacterial ability after the infrared light disappears.
[0039] Example 1:
[0040] (1) Synthesis with eutectic solvent: 2 mol of ethylene glycol and 1 mol of choline chloride were stirred continuously in a water bath at 70°C for several hours until a clear and transparent solution was obtained;
[0041] (2) Annealing treatment of molybdenum disulfide: under nitrogen protection, molybdenum disulfide was annealed at 300°C for 2 hours to obtain molybdenum disulfide powder with S vacancies;
[0042] (3) Liquid phase stripping of molybdenum disulfide: 1g of molybdenum disulfide powder with S vacancy, 150mg of alkali lignin, and 100g of Milli-Q ultrapure water were mixed and treated with ultrasonic treatment at 20kHz, 40kHz and 60kHz at 30℃ for 3 hours. The unstripped molybdenum disulfide was removed by centrifugation at 10000rpm to obtain a two-dimensional molybdenum disulfide and lignin suspension. The concentration of the two-dimensional molybdenum disulfide suspension was 1.713mg / mL by ultraviolet spectrophotometry.
[0043] (4) Preparation of photoresponsive antibacterial composite film: 2 mL of two-dimensional molybdenum disulfide and lignin suspension, 10 mL of polyvinyl alcohol solution of a certain concentration, and 200 μL of eutectic solvent were mixed and then dried at 37°C for 24 hours after being placed in a water bath at 90°C for 30 minutes.
[0044] Example 2:
[0045] (1) Synthesis with eutectic solvent: 2 mol of ethylene glycol and 1 mol of choline chloride were stirred continuously in a water bath at 70°C for several hours until a clear and transparent solution was obtained;
[0046] (2) Annealing treatment of molybdenum disulfide: under nitrogen protection, molybdenum disulfide was annealed at 300°C for 2 hours to obtain molybdenum disulfide powder with S vacancies;
[0047] (3) Liquid phase stripping of molybdenum disulfide: 1g of molybdenum disulfide powder with S vacancy, 100mg of alkali lignin, and 100g of Milli-Q ultrapure water were mixed and treated with ultrasonic treatment at 20kHz, 40kHz, and 60kHz at 30℃ for 3 hours. The unstripped molybdenum disulfide was removed by centrifugation at 10000rpm to obtain a two-dimensional molybdenum disulfide and lignin suspension. The concentration of the two-dimensional molybdenum disulfide suspension was 1.702mg / mL by ultraviolet spectrophotometry.
[0048] (4) Preparation of photoresponsive antibacterial composite film: 2 mL of two-dimensional molybdenum disulfide and lignin suspension, 10 mL of polyvinyl alcohol solution of a certain concentration, and 200 μL of eutectic solvent were mixed and then dried at 37°C for 24 hours after being placed in a water bath at 90°C for 30 minutes.
[0049] Example 3:
[0050] (1) Synthesis with eutectic solvent: 2 mol of ethylene glycol and 1 mol of choline chloride were stirred continuously in a water bath at 70°C for several hours until a clear and transparent solution was obtained;
[0051] (2) Annealing treatment of molybdenum disulfide: under nitrogen protection, molybdenum disulfide was annealed at 300°C for 2 hours to obtain molybdenum disulfide powder with S vacancies;
[0052] (3) Liquid phase stripping of molybdenum disulfide: 1g of molybdenum disulfide powder with S vacancies, 50mg of alkali lignin, and 100g of Milli-Q ultrapure water were mixed and treated with ultrasonic treatment at 20kHz, 40kHz, and 60kHz at 30℃ for 3 hours. The unstripped molybdenum disulfide was removed by centrifugation at 10000rpm to obtain a two-dimensional molybdenum disulfide and lignin suspension. The concentration of the two-dimensional molybdenum disulfide suspension was 1.489mg / mL by ultraviolet spectrophotometry.
[0053] (4) Preparation of photoresponsive antibacterial composite film: 2 mL of two-dimensional molybdenum disulfide and lignin suspension, 10 mL of polyvinyl alcohol solution of a certain concentration, and 200 μL of eutectic solvent are mixed in a certain volume ratio, and after being bathed in a water bath at 90°C for 30 minutes, the film is dried at 37°C for 24 hours to obtain photoresponsive antibacterial composite film.
[0054] Comparative Example 1:
[0055] (1) Synthesis with eutectic solvent: 2 mol of ethylene glycol and 1 mol of choline chloride were stirred continuously in a water bath at 70°C for several hours until a clear and transparent solution was obtained;
[0056] (2) Annealing treatment of molybdenum disulfide: under nitrogen protection, molybdenum disulfide was annealed at 300°C for 2 hours to obtain molybdenum disulfide powder with S vacancies;
[0057] (3) Liquid phase stripping of molybdenum disulfide: 1g of molybdenum disulfide powder with S vacancies, 0mg of alkali lignin, and 100g of Milli-Q ultrapure water were mixed and treated with ultrasonic treatment at 20kHz, 40kHz, and 60kHz at 30℃ for 3 hours. The unstripped molybdenum disulfide was removed by centrifugation at 10000rpm to obtain a two-dimensional molybdenum disulfide and lignin suspension. The concentration of the two-dimensional molybdenum disulfide suspension was 0.882mg / mL by ultraviolet spectrophotometry.
[0058] (4) Preparation of photoresponsive antibacterial composite film: 2 mL of two-dimensional molybdenum disulfide suspension, 10 mL of polyvinyl alcohol solution of a certain concentration, and 200 μL of eutectic solvent are mixed in a certain volume ratio, and after being bathed in water at 90°C for 30 minutes, the film is dried at 37°C for 24 hours to obtain photoresponsive antibacterial composite film.
[0059] Comparative Example 2
[0060] (1) Synthesis with eutectic solvent: 2 mol of ethylene glycol and 1 mol of choline chloride were stirred continuously in a water bath at 70°C for several hours until a clear and transparent solution was obtained;
[0061] (2) Annealing treatment of molybdenum disulfide: under nitrogen protection, molybdenum disulfide was annealed at 300°C for 2 hours to obtain molybdenum disulfide powder with S vacancies;
[0062] (3) Liquid phase stripping of molybdenum disulfide: 1g of molybdenum disulfide powder with S vacancies, 100mg of alkali lignin, and 100g of Milli-Q ultrapure water were mixed and treated with ultrasonic treatment at 20kHz, 40kHz, and 60kHz at 30℃ for 3 hours. The unstripped molybdenum disulfide was removed by centrifugation at 10000rpm to obtain a two-dimensional molybdenum disulfide and lignin suspension. The concentration of the two-dimensional molybdenum disulfide suspension was 1.698mg / mL by ultraviolet spectrophotometry.
[0063] (4) Preparation of photoresponsive antibacterial composite film: 2 mL of two-dimensional molybdenum disulfide suspension, 10 mL of polyvinyl alcohol solution of a certain concentration, and 0 μL of eutectic solvent were mixed and then dried at 37°C for 24 hours in a water bath at 90°C to obtain photoresponsive antibacterial composite film.
Claims
1. A method for preparing a two-dimensional molybdenum disulfide-based photoresponsive antibacterial composite film, characterized in that... Follow these steps: (1) Synthesis of eutectic solvent: The eutectic solvent is ethylene glycol: choline chloride is stirred at 70°C for several hours in a certain molar ratio until a uniform and transparent liquid is formed; (2) Annealing treatment of molybdenum disulfide: under nitrogen protection, molybdenum disulfide is annealed at a certain temperature for several hours to obtain molybdenum disulfide powder with S vacancies; (3) Liquid phase stripping of molybdenum disulfide: Molybdenum disulfide powder with S vacancies in step (2), alkali lignin, and Milli-Q ultrapure water are mixed in a certain mass ratio, treated with tri-frequency ultrasonication at 30°C for 3 hours, and the unstripped molybdenum disulfide is removed by centrifugation at 10000rpm to obtain a two-dimensional molybdenum disulfide and lignin suspension. (4) Preparation of photoresponsive antibacterial composite film: In step (3), two-dimensional molybdenum disulfide and lignin suspension, a certain concentration of polyvinyl alcohol solution and eutectic solvent are mixed in a certain volume ratio, and after being bathed in a water bath at 90°C for 30 minutes, the film is dried at 37°C for 24 hours to obtain photoresponsive antibacterial composite film.
2. The method for preparing a two-dimensional molybdenum disulfide-based photoresponsive antibacterial composite film according to claim 1, characterized in that... The molar ratio of ethylene glycol and choline chloride mentioned in step (1) is 2:
1.
3. The method for preparing a two-dimensional molybdenum disulfide-based photoresponsive antibacterial composite film according to claim 1, characterized in that... In step (2), the annealing temperature is 300℃ and the annealing time is 2 hours.
4. The method for preparing a two-dimensional molybdenum disulfide-based photoresponsive antibacterial composite film according to claim 1, characterized in that... Step (3) The mass ratio of molybdenum disulfide powder, alkali lignin and Milli-Q ultrapure water is 1:0.05~0.15:100; the ultrasonic frequency is 20kHz, 40kHz and 60kHz, the output power is 600W, and the switching pulse is 4 / 1s.
5. The method for preparing a two-dimensional molybdenum disulfide-based photoresponsive antibacterial composite film according to claim 1, characterized in that... The polyvinyl alcohol concentration in step (4) is 5%, and the solvent is Milli-Q ultrapure water, two-dimensional molybdenum disulfide and lignin suspension, polyvinyl alcohol, and the volume ratio of the eutectic solvent is 2:10:0.2.